Оцінка якості функціонування інтегрованих інформаційних систем - Tanyanskii, S. S.; Grinyova, Ye. Ye. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The basic information system characteristics influencing the quality of the system work in an integrated environment are considered. Parameters of the quality of data processing and the program applications that are part of the information system are determined. The problem of multicriterial estimation of the quality of information systems and a model of decision-making for the selection of the best variant of integration are described.